EARLY DATING IN DIGITAL NATIVE ERA: DAMPAK KONTEN DIGITAL TERHADAP FENOMENA TREN PACARAN DINI GEN ALPHA DI SEKOLAH DASAR - Surya, Ade; Enjang Yusup Ali; Dety Amelia Karlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Various challenges in character education in elementary schools come along with digitalization, including the phenomenon of early dating carried out by the alpha generation in elementary schools. They are digital natives who are inseparable from the digital content that is increasingly consumed. As a result, they have a tendency to imitate adult behavior, in this case dating. This study attempts to highlight the impact of digital content on the phenomenon of the early dating trend of the alpha generation in elementary schools. The method used is a phenomenological study with a qualitative approach, with data collection techniques in the form of interviews with 34 subjects, observation, and documentation. The data collection was carried out in three schools with their own characteristics but with one link, namely digitalized schools, whether in cities, transition areas or villages. The results show that providing access to digitalization for children also brings digital content that triggers early dating behavior at elementary school age. Including creating the content itself. Various follow-up problems also arise such as decreased focus on learning, emotionality, and even violating religious rules. In this context, character education and guidance from elementary school teachers and parents are very necessary. In conditions on the ground, several strategies and solutions have been and will be implemented, such as monitoring, digital protection, religious education, sexual education, and collaborating with external parties. In conclusion, early dating is an unavoidable phenomenon in the digital era, but schools and families can collaborate together in preventing and handling it.